Performance and Capacity Building of Village Food Institutions - Purnomo, Didit; Arif, Muhammad; Hasmarini, Maulidyah Indira; Rafiuddin, Mohammad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
This study aimed to analyze the performance of village food institutions by performing assessment to their efficiency level. These food institutions are the Community Food Distribution Institution (LDPM) and the Village Community Food Reserves (LPMD). The benefits gained from this assessment is the determination of the most efficient and inefficient performance of those institutions. Based on the efficiency level, the model of capacity building of each food institution can be determined. Survey approach was used with farmers and farmer groups incorporated in food institutions as the respondents. Analysis study in this research used quantitative analysis and was reaffirmed by in-depth interview technique. Activity was initiated by identifying each food institution in the study sample site. It revealed that the performances and conditions of each food institution are diverse. The potential and role of the Village Food Institutionsbased on the achieved level of efficiency, and also a model of improving food barns and a resilience of farmers community and institution, particularly in realizing the achievement of local food security.